اليقظة المعلوماتية كآلية لتحسين الصورة الذهنية للمؤسسة - مناصري نسيمة; حاج سالم عطيه (University of Eloued جامعة الوادي, 2024)
نهدف من خلال هذا المقال إلى تبيان كيفية استفادة المؤسسة من مخرجات نشاط اليقظة المعلوماتية في تحسين صورتها الذهنية، من خلال رصد وتحليل محتوى معلوماتي متنوع ومتداول عبر شبكات التواصل الاجتماعي. حيث توصلت هذه الورقة البحثية إلى أن نجاح أو فشل المؤسسة في الحفاظ على صورتها أو تحسينها يتوقف على إمكانية تكيفها مع ديناميكية وعناصر البيئة المعلوماتية التي تنشط فيها، وفي مقدمتها المحتوى المتداول عبر شبكات التواصل الاجتماعي وسبيلها لتحقيق ذلك نشاط اليقظة المعلوماتية الذي يمكنها من تحصين نفسها من تغيرات بيئتها بالشكل الذي يضمن استقرار صورتها وتحسينها. Abstract : Through this article, we aim to show how the institution benefits from the outputs of information monitoring activity in improving its mental image by monitoring and analysing diverse information content traded across social media . This paper found that the success or failure of the institution to maintain or improve its image depends on the possibility of adapting it to the dynamic and modernized information environment in which it is active. First of all, the content circulating through social media and the way to do soi, is the information monitoring activity that enables it to immunize itself from changes in its environment in a way that ensures stability and improvement of its image
Keywords: المسح البيئي; المعلومة; اليقظة المعلوماتية; شبكات التواصل الاجتماعي; الصورة الذهنية; Environmental Survey; Information; Information Monitoring; Social Media; Mental Image